2016
DOI: 10.5935/1981-2965.20160055
|View full text |Cite
|
Sign up to set email alerts
|

Infrared thermography as diagnostic tool for bovine subclinical mastitis detection

Abstract: Forty-eight Holstein cows were assessed using infrared thermography as noninvasive diagnostic tool for subclinical mastitis detection. The temperature analysis of animals negative in the California Mastitis Test has evidenced a difference between the mean temperatures in the front and rear quarters (p=0.001). The infrared thermography comparison between the rear quarters of animals positive and negative in the California Mastitis Test has not shown any difference (p=0.236), but the comparison of results of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
4
0
3
Order By: Relevance
“…Infrared thermography can be defined as a non-invasive technique for perceiving the surface temperature of a body, since all bodies with temperature above the absolute zero (0 K) emit thermal radiation (Roberto & Souza, 2014). Among some studies that have assessed udder temperature variation in lactating cows, the one by Digiovani et al (2016) stands out for using thermal images as a diagnosis tool to detect subclinical mastitis, finding differences between the temperature of healthy udders and of those with subclinical mastitis. Pezeshki et al (2011) studied variations in the inflammatory dynamic of Escherichia Coli using infrared thermography and found that the technique was capable of detecting temperature changes on the udder skin surface.…”
Section: Introductionmentioning
confidence: 99%
“…Infrared thermography can be defined as a non-invasive technique for perceiving the surface temperature of a body, since all bodies with temperature above the absolute zero (0 K) emit thermal radiation (Roberto & Souza, 2014). Among some studies that have assessed udder temperature variation in lactating cows, the one by Digiovani et al (2016) stands out for using thermal images as a diagnosis tool to detect subclinical mastitis, finding differences between the temperature of healthy udders and of those with subclinical mastitis. Pezeshki et al (2011) studied variations in the inflammatory dynamic of Escherichia Coli using infrared thermography and found that the technique was capable of detecting temperature changes on the udder skin surface.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal images were obtained from an infrared thermographic camera, with resolution of 0.01º C, focal length of 1.0 m, and emissivity adjusted to 0.97 (Digiovani et al, 2016). The images were taken in the morning, before the first milking, between 05:00 and 07:00 (because it is when room temperature is lower and does not interfere with the image analysis process) on the following quarters: front left side (FL), front right side (FR), rear left side (RL) and rear right side (RR), with four images per animal, totaling 96 thermal images for analysis of mammary quarters (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…The application of this technique, with an emphasis on detecting early inflammatory cases, has been reported in some studies, such as Polat et al (2010), Pezeshki et al (2011) and Digiovani et al (2016), which investigated thermal images as a diagnosis tool for detecting subclinical mastitis and verified that thermography allowed identifying temperature changes on the animals' udder skin surface. Gloster, Ebert, Gubbins, Bashiruddin, and Paton (2011) and Redaelli et al (2014) proposed analyzing thermal images as a preventive method, since it detects temperature changes before the onset of the first clinical signs, acting as a warning sign for animal observation.…”
Section: Introductionmentioning
confidence: 92%
“…As imagens térmicas do úbere dos animais foram obtidas a partir de uma câmera termográfica por infravermelho, com resolução de 0,01ºC, distância focal de 1,0 m e emissividade ajustada para 0,97 de acordo com o aplicativo Flir QuickReport (Digiovani et. al, 2016).…”
Section: Methodsunclassified